PENGARUH PENGGUNAAN SISTEM INFORMASI TERHADAP KINERJA KARYAWAN (STUDI KASUS: PT. INDOSAT JAKARTA) - ENI IRFIANI (LPPM Universitas Bina Sarana Informatika, 2015)
This study aims to examine the influence of the information system at PT. Indosat using Online DJ on employee performance. This study was conducted to investigate whether Internet-based information system at PT. Indosat, known as DJ Online influence on employee performance. The problems that must be resolved is how the application of information systems DJ Online and conditions of the performance of employees of PT. Indosat in serving customers Multimedia, Infrastructure, Data and Internet Service (MIDI). The scale of measurement using a Likert scale with the number of questionnaires as much as 36 respondents. Research methodology with quantitative research and primary data processing using SPSS software. From the test results are to be obtained regression results indicate the magnitude of Adjusted R Square of 0144. It shows 14.4% variable use of information systems is influenced by the performance of employees, while 85.6% is influenced by other variables outside of the variables used. Variable use of information systems has a p-value 0.022 significant meaning. The results showed that the information system DJ Online significant influence on employee performance.